Humor and poignancy: Exploring narrative pathways to face death and bereavement - Fitzgerald, Kaitlin; Francemone, C. Joseph; Grizzard, Matthew (Frontiers in Communication, 2022)
Themes of death and grief emerge in media entertainment in ways that are both poignant and humorous. In this experimental study, we extend research on eudaimonic narratives about death to consider those that are hedonic. Participants read a story about a woman giving a eulogy for her friend that was manipulated to be either poignant-focused or humor-focused. The narrative conditions elicited similar levels of narrative engagement and appreciation, but the humor-focused narrative elicited more enjoyment than the poignant-focused narrative. Connectedness did not differ between conditions. However, the humor-focused narrative elicited more death acceptance when controlling for participants’ personal loss acceptance and grief severity, and individual differences in the dark tetrad personality traits, trait depression, and religious upbringing. We tested these effects in an integrated path model and found that the model fit the data well and the narrative pathways explained variance in both death acceptance and connectedness. Our findings have implications for how death and grief are depicted in media entertainment: namely, that death is an inherently poignant topic and the addition of humorous elements in bereavement narratives may be especially effective in increasing death acceptance. Keywords: narrative, humor, poignancy, death acceptance, grief, loss, enjoyment, appreciation